Complete agenesis of the right hemi-diaphragm in an adult: case report and literature review.: Diaphragmatic Agenesis - Taha, Abdulsalam Yaseen; Kaznazani, Kalandar (Journal of the Faculty of Medicine Baghdad, 2021)
Congenital agenesis of the hemi-diaphragm (AHD) in adults is rare and exceedingly so on the right side. Since its first recognition in 1959, no more than 9 cases have been published in the English literature by the year 2016. “Partial diaphragm agenesis” is actually large congenital diaphragmatic hernia (CDH) rather than true AHD. Respiratory compromise is the likely presentation, however, patients may survive for years without symptoms. Despite a straightforward clinical and radiographic diagnosis of AHD, the best method of repair is controversial. Herein, we present a case of complete right-sided AHD in a man of 54 diagnosed on surgical exploration 16 years earlier. Despite trans-thoracic mesh repair, the patient experienced just a modest improvement of his shortness of breath (SOB). Though the liver persisted high in the chest as shown by serial CT scans of the chest, polypropylene mesh was effective in preventing further visceral herniation. Adult patients with right-sided AHD always deserve operative intervention to avoid the potential complications.